Superhighways for Open and Distance Learning - Christos Bouras; Paul Spirakis; P Lampsas (1997 EDEN Conference, Budapest, Hungary, 1997)
An educational information network, is a multimedia network with a centralized architecture for the provision of educational services. The educational services comprise basic network applications (such as multimedia e-mail, fora for debates on educational subjects, access to already existing information), video distribution of multimedia lessons and a custom developed teletraining tool for the conduction of lessons over a broadband networking infrastructure. The suitability of the widely available broadband networking technologies (ATM, ISDN), as opposed to the alternative of using already existing networking infrastructure (Internet, CATV), for the implementation of educational networks for the realization of an Open and Distance Learning Environment will be examined. More specifically the types of educational services that can be best hosted by each technology and the costs as opposed to the maturity for the deployment of each networking technology will be cited. Finally, a proposal for an implementation scheme of an educational information network, concerning the appropriate (and cost effective) networking infrastructure that can best accommodate the aforementioned educational services will be elaborated.